â€œKLASTER BERDAYAâ€ PROGRAM AS COMMUNITY-BASED EMPOWERMENT MODEL (STUDY IN NATIONAL HUMANITARIAN FOUNDATION PKPU) - Nisak, Khoirun (Jurnal Ekonomi & Studi Pembangunan, 2017)
Indonesia is facing a serious problem in poverty. In March 2016, the data released by Central Statistics Agency (BPS) showed that 28.01 million people or 10.86% of total Indonesianâ€™s population are living under the poverty threshold. The number of poor people in rural area are higher than in urban area. In response to this fact, as a noncommercial organization that focus on community empowerment, national humanitarian foundation PKPU released a program called â€œKlaster Berdayaâ€. The objective of this program are to build self-reliance of society in improving their quality of life and to reduce poverty as well. One of the pilot project of Klaster Berdaya is located in Klanting Village, Sukodono Sub district, Lumajang Regency, East Java. The programs are conducted by providing scholarship and raising livestock. The scholarship is given for students who have outstanding academic achievement but come from low-income family.